Deposition of TaN Film on Commercial Pure Titanium Disk by Modified Reactive Plasma Sputtering Technique - Deposition of TaN Film on Commercial Pure Titanium Disk by Modified Reactive Plasma Sputtering Techn (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The new trend of implants is to find materials which accelerate bone formation at bone implant interface and improve Osseo integration to provide immediate or early loading after placement and eliminate waiting period which is uncomfortable and disturbs patients. Titanium as an implant material still need some improvement of surface properties physically and chemically. Tantalum which is gaining more attention as a new metallic biomaterial. Coating layer over implant is an important way for improvement of surface properties of titanium. Plasma used for surface modification, has several advantages such as changing surface topography, increasing surface roughness and in increasing the wettability of the surface.Aim of study: To evaluate the effect of TaN coating by modified plasma sputtering technique of commercially pure titanium disk on wettability, surface roughness, surface chemical composition in comparison to non-coated surface.Materials and method: Two groups were tested in this study which include non -coated commercial pure titanium disks and coated commercial pure titanium with TaN. Modified reactive plasma sputtering apparatus was used to coat CpTi with TaN at 4, 6 &8, h. Surface characterization by x-ray diffraction (XRD) analysis, scanning electron microscope (SEM), energy dispersive spectroscopy(EDS), contact angle measurement, were carried out for coated and uncoated disks.Results: The result of coating specimen with TaN at times (4,6&8) h showed that 8 h coating time was the best time. And this was according to the results of X-ray diffraction analysis which show a new peak formation of Ta N coated CpTi disk which was not present in non- coated CpTi disk. The results of wettability test for CpTi disk coated with TaN disk was more than wettability of non- coated CpTi disk. Surface Roughness was more and better distributed in CpTi coated with TaN disk than non- coated one which appear clearly in electron microscope.